Os estágios iniciais do desenvolvimento do zebrafish como modelo alternativo para predizer a toxicidade oral aguda in vivo - Prado, Lara Barroso Brito (2021)
Zebrafish (Danio rerio) early-life stages offer a complex and multicellular system integrating various tissues and differentiation processes. In addition, the zebrafish embryos are structurally and functionally similar to vertebrates, including humans. The acute toxicity test with zebrafish embryos and larvae is already worldwide recognized as an alternative model for ecotoxicological assessment, but it is not include in normative of the Council fot the Control of Animal Experimentation (CONCEA), wich recognize the use of alternative methods validated in research activities in Brazil. This organism model can filling the gap between conventional in vitro and in vivo tests for extrapolation of data for humans, the present study aimed to assess the acute toxicity of substances with different Global Harmonization System (GHS) categories using zebrafish early-life stage to determine LC50 values and compared with in vivo (LD50) acute oral toxicity data from literature, in order to generate a model to prediction acute oral toxicity. This prediction model was evaluated by the application of a drug candidate (LQFM 021). Fifteen substances were evaluated by Fish Embryo Acute Toxicity (FET) test (OECD 236). Parameter evaluated was lethal and sublethal effects after 96 h of exposure. A linear regression- model using the log-transformed of the LC50 values and LD50 was generated for the estimated of LD50 from LC50 values. This model resulted in the following equation Log LD50 (mg/kg) = 0.5749 x log LC50 (mg/L) + 1.284. The method domain of application was 53.33% and the R2 was 0,66. Sublethal effects indicate that substances more toxic presented more abnormalities. The DL50 predicted with FET testing LQFM 021, which classified as category 4 in GHS acute oral systemic toxicity assessment, was of 408.52 mg/kg, which also classified as Category 4. In this work, Quantitative Activity-Activity Relationship (QAAR) models were also developed, based on the data obtained in the FET test with zebrafish. This model using seven toxicological descriptors generated statistically predictive models with R2 values ranging from 0.80 to 0.95 and in combination with the Random Forest method it presented the best performance in the prediction of acute oral toxicity in vivo. Therefore, our results suggest that early-life stages of zebrafish could be at least a refinement in the sense of the principles of the 3R’s to predict acute oral toxicity in vivo, being as an intermediary in the preclinical evaluation between in vitro and in vitro.